Relationship between petrographic pore types and core measurements in sandstones of the Monserrate formation, upper Magdalena valley, Colombia - Cobaleda, G.; Ehrlich, R.; Ferm, J. Barclay (CT&F - Ciencia, Tecnología y Futuro, 1997)
Patterns of porosity in sandstones of the Monserrate Formation (Upper Magdalena Valley) exposed in polished blocks have been digitally recorded using an image processor coupled to a scanning electron microscope operated in backscatter electron mode. Additionally, porosity, permeability and response to mercury injection-capillary pressure tests were measured on some of the imaged samples. Porosity patterns were evaluated via an erosion/dilation-differencing image-processing algorithm and then classified by the selftraining classifier, SAWVEC. Changes in the resulting pore type proportions were strongly associated with changes in the mercury porosimetry curves. From the image processing data, five pore types, sufficient to include all of the variability in size and shape of the patterns of porosity, were identified. Variations in the number of pores of each type per unit cross sectional area were related to variations in permeability. The resultant relationships with mercury porosimetry demonstrated that pores of the same type tend to form microcircuits characterized by a limited throat size range. Permeability modeling showed that intergranular Pore Types 2 and 4 (secondary porosity resulting from carbonate dissolution) are responsible for permeability in the 0,01 -0,1 0 Darcy range. Type 5 pores (large molds) slightly contribute to permeability, except in coarse grained rocks where they are efficiently connected by microfractures.